The Influence of Organizational Culture, Work Motivation and Leadership Style on Improving Employee Performance at PT Mutiara Mukti Farma Medan - Ananda, Julia; Sihotang, Fitri Dwisari; Hutabarat, Darwis; Siregar, Ina Namora Putri; Sirait, Dita Eka Pertiwi (Lembaga Riset Ilmiah, 2024)
The aim of this research is see is culture organization, motivation work, and style leadership influence performance employees of PT Mutiara Mukti Farma Medan. With use method quantitative, including analysis statistics descriptive. Population that is employee PT Pearl Mukti Pharma Medan amount 300 person and technique determination sample with formula slovin random sampling and selected 75 sample. Data is collected through observation, interviews, questionnaires, and journals other. Study This produce conclusion that is culture organization give influence significant increase​ performance of PT Mutiara Mukti Farma Medan. Motivation Work give influence significant increase​ performance of PT Mutiara Mukti Farma Medan. Leadership style give influence significant increase​ performance of PT Mutiara Mukti Farma Medan. By simultaneous culture organization, motivation work and style leadership influential positive and significant increase​ PT employee performance Mutiara Mukti Farma Medan. Determination shows results of 0.665 which means culture organization, motivation Work And style leadership contribute to enhancement performance PT Mutiara employees Mukti Pharma Medan as big as 66.5 %.